Opportunities and challenges for the successful development of Ukrainian technology companies - Omelchenko, Ivan (My University, 2023)
The article discusses the promising development markets for Ukrainian tech companies, with a focus on why Western markets are the best way to develop and why Ukrainian companies are attractive to Western businesses. It also delves into the main challenges faced by domestic companies when expanding into Western markets. The article provides insights and recommendations for Ukrainian tech companies looking to expand their business to Western markets.
Keywords: Ukrainian tech companies; marketing strategy; Go-To-Marketing strategy; company positioning; Western markets expansion